1990
DOI: 10.2134/jeq1990.00472425001900030016x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Leaching from Systematically Tiled Potato Fields in New Brunswick, Canada

Abstract: Flow volumes and NO 3 -N concentrations of drain discharge from five systematically tiled, commercial potato (Solatium tuberosum L.) fields were measured from April to December, 1987 and 1988, to assess the potential for NO 3 -N leaching associated with current production practices. The sites, located in New Brunswick, Canada, ranged from 3 to 10 ha and varied in fertilizer application rate, cropping practices, rainfall, and duration of data collection (the latter due to site access difficulties in the spring)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 0 publications
5
28
1
Order By: Relevance
“…The only exception was evidence of downward movement of soil NO 3 --N within the hill observed at topkill in 1999 in response to the substantially above-average rainfall in September of 1999. This is consistent with previous studies in non-irrigated potato and corn fields in Atlantic Canada, where most nitrate leaching occurred during the fall and winter period (Milburn et al 1990;Milburn and Richards 1994;Milburn et al 1997).…”
Section: Discussionsupporting
confidence: 92%
“…The only exception was evidence of downward movement of soil NO 3 --N within the hill observed at topkill in 1999 in response to the substantially above-average rainfall in September of 1999. This is consistent with previous studies in non-irrigated potato and corn fields in Atlantic Canada, where most nitrate leaching occurred during the fall and winter period (Milburn et al 1990;Milburn and Richards 1994;Milburn et al 1997).…”
Section: Discussionsupporting
confidence: 92%
“…This is because the soil nitrogen concentration was reduced by then, leading to a low nitrate concentration in the meltwater moving through the macropores to the drain. Smettem et al (1983), Milburn et al (1990), and Magesan et al (1995 reported similar observations.…”
Section: Mechanism Of Nitrate Leaching By Subsurface Drainagesupporting
confidence: 65%
“…In Atlantic Canada for example, large quantities of nitrates can leach from soils cropped to potatoes (Solanum tuberosum L.) both during the growing season and in the following rotation year (Milburn et al 1990). Studies conducted on potatoes in Maine, Ontario, and New York show that only about 45 to 60% of N applied at planting with rates of 160 to 225 kg N ha -1 is recovered in the tubers (Bouldin and Selleck 1977;Cameron et al 1978).…”
Section: Mots Clésmentioning
confidence: 99%